(untitled) (Research, Society and Development, 2022)
The present study aimed to collect and analyze statistical data regarding cases of syphilis in pregnant women, as well as changes in clinical classifications in the previous period and during the pandemic in Brazil. For the construction of the article, an ecological time series study was carried out, using data on the incidence and clinical changes of syphilis in pregnant women, aligned with the regional geographic unit to which they belonged, in the period from 2018 to 2021. According to the data obtained, we see a large drop between the years 2020 and 2021 in cases of syphilis in pregnant women, a drop of 51.42%, possibly due to the prioritization of emergencies and the reduction in the risk of transmission of SARS-CoV-2 in health services, social isolation, underreporting and exacerbation of social inequities during the pandemic, reduction in the birth rate, reduction of socialization due to isolation during the pandemic. This discovery causes several future complications for both patients and health service providers, which will eventually bring more costs to the system, because if there was an early discovery of this disease, a less invasive, painful treatment could be performed, with a greater chance of cure. It is necessary to intensify the alert for citizens not to neglect their health amid the fear implanted in the pandemic, so that it is possible to identify, treat and consequently prevent new lives from being taken in the Brazilian population.